PENGARUH PENYAJIAN LAPORAN KEUANGAN, VALUE FOR MONEY, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Kasus SKPD Pemerintah Daerah Kabupaten Pekalongan Tahun 2018) - Sri Mulyani, 14.05.52.0283; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2018)
This study is intended to identify the impact of presentation of the financial statement, value for money, the internal control, and the accessibility to the financial statement on the accountability of the regional financial management. This study was conducted at SKPD of Pekalongan Regency. This study is a quantitative one, in which primary data were used. The respondents were the staff of the financial division and financial administrative division employed at each department ‘satuan kerja perangkat daerah’ of Pekalongan Regency. The convenience sampling technique was used and 93 respondents were involved. The data were collected through survey using the questionnaire distributed to the respondents. The data scale was measured using likert scale. Analyzes influence between variable by using method of multiple linear regression analysis. The results of the study showed that presentation of the financial statement, the internal control, and the accessibility to the financial statement positively affected the accountability of the regional financial management. Value for money no affect the accountability of the regional financial management. Keywords:Presentation Of The Financial Statement, Value For Money, The Internal Control, The Accessibility To The Financial Statement And Accountability Of The Regional Financial Management